Mathematical and experimental study of the direct contact membrane distillation method for desalination using a hydrophobic electrospun nanofibers membrane - Safi, Nawras N.; Waisi, Basma I. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This paper examines the performance of a Direct Contact Membrane Distillation (DCMD) system experimentally and theoretically. The system uses a super hydrophobic electrospun nanofiber membrane to desalinate water. Investigations were carried out into how the feed concentration, feed flow rate, and feed temperature affected permeate flux. as system operating parameters to aid in comprehending the factors impacting the DCMD process. The application of DOE and Taguchi methods achieved statistical optimization of the DCMD process's performance. In addition, the study of mass and heat transport in DCMD was described by a theoretical model. While the feed concentration (0- 210 g/L) significantly affected flux, the feed's temperature (35-55 °C) and flow rate (0.2-0.6 L/min) mostly dominated the impact on system performance. The created model numerically solved the DCMD process using MATLAB software, describing it as a system of nonlinear equations. Various operating conditions were used to investigate the efficiency of the superhydrophobic electrospun nanofiber membrane in treating 210 g/L NaCl salt water. Changing the feed temperature and concentration affected the hypothetically suggested path across the membrane, according to the simulation results presented in this paper. Excellent agreement was observed between the experiment results and the constructed model's predicted results. Every instance maintained a high salt rejection rate (over 99.9%). The DCMD produced a gain output ratio (GOR) of 0.87 and a temperature polarization coefficient of 0.78 to 0.91. The system achieved a maximum thermal efficiency of 73.5%. The optimal parameters, which are 70 g/L, 0.6 L/min, and 55°C.